The Potential Of The Dried Fish Business In Encouraging The Economic Welfare Of The Kuantan Village Community From An Islamic Business Perspective - Roswandi, Risvan Akhir (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2025)
This study aims to examine the potential of the dried fish business to enhance the economic welfare of the Kuantan Tenang Village community and to review its business practices from an Islamic perspective. The dried fish enterprise is among the emerging economic sectors within this village, owing to the plentiful freshwater fish resources. Employing a descriptive qualitative methodology, data were gathered through observation, interviews, and documentation from business stakeholders and community leaders. The findings indicate that the dried fish industry in Kuantan Tenang Village possesses considerable potential to bolster the community's economy, supported by the availability of raw materials, local labor, and established processing traditions. Although primarily traditional, this enterprise can serve as a source of income and employment. From an Islamic business standpoint, its practices adhere to the principles of halal, justice (al-'adl), trustworthiness (amanah), and provide maslahah (benefit). Consequently, in addition to economic benefits, this enterprise also holds spiritual significance and the capacity to confer blessings upon its practitioners.